2019
DOI: 10.3390/ma12193102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zn Content on the Microstructure and Mechanical Properties of Mg–Al–Sn–Mn Alloys

Abstract: High performance Mg–6Al–3Sn–0.25Mn–xZn alloys (x = 0, 0.5, 1.0, 1.5, and 2.0 wt %) without rare earth were designed. The effects of different Zn contents on the microstructure and mechanical properties were systematically investigated. The addition of Zn obviously refines the as-cast alloys dendritic structure because of the increase in the number in the second phase. For the as-extruded alloys, an appropriate amount of Zn promotes complete recrystallization, thus increasing the grain size. As the Zn content i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…On the other hand, When the Al alloy content of Zn is lower than 2 wt-%, the influence of Zn in the grain size of the Al matrix becomes ambiguous. The mean grains size in an Mg–Al-based alloy with 0.5 wt-% Zn, 1 wt-% Zn, 1.5 wt-% Zn and 2 wt-% Zn were fluctuated between 4.8, 9.4, 9.0 and 4.8 µm, respectively [27]. Similarly, Chuvil'deev et al reported that with increasing the content of Zn from 1 wt-% to 2 wt-%, the average grain sizes in a fine-grained Al alloy slightly increased from 1.7 to 1.9 µm and then decreased to 1.5 µm when the content of Zn reached 3 wt-% [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, When the Al alloy content of Zn is lower than 2 wt-%, the influence of Zn in the grain size of the Al matrix becomes ambiguous. The mean grains size in an Mg–Al-based alloy with 0.5 wt-% Zn, 1 wt-% Zn, 1.5 wt-% Zn and 2 wt-% Zn were fluctuated between 4.8, 9.4, 9.0 and 4.8 µm, respectively [27]. Similarly, Chuvil'deev et al reported that with increasing the content of Zn from 1 wt-% to 2 wt-%, the average grain sizes in a fine-grained Al alloy slightly increased from 1.7 to 1.9 µm and then decreased to 1.5 µm when the content of Zn reached 3 wt-% [28].…”
Section: Resultsmentioning
confidence: 99%
“…According to Gardner and Grimes, the recrystallisation temperature of Al decreases continuously with the addition of Zn until the solid solubility limit of Zn in Al is reached [29]. Also, Zhao et al proved that Zn progressively promoted the recrystallisation of Mg–Al-based alloy [27]. The grain orientation spread (GOS) mapping is a grain boundary-based approach obtained through EBSD.…”
Section: Resultsmentioning
confidence: 99%